2021
DOI: 10.1212/wnl.0000000000011655
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Yield of Whole Genome Sequencing After Nondiagnostic Exome Sequencing or Gene Panel in Developmental and Epileptic Encephalopathies

Abstract: ObjectiveTo assess the benefits and limitations of whole genome sequencing (WGS) compared to exome sequencing (ES) or multigene panel (MGP) in the molecular diagnosis of developmental and epileptic encephalopathies (DEE).MethodsWe performed WGS of 30 comprehensively phenotyped DEE patient trios that were undiagnosed after first-tier testing, including chromosomal microarray and either research ES (n = 15) or diagnostic MGP (n = 15).ResultsEight diagnoses were made in the 15 individuals who received prior ES (5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(64 citation statements)
references
References 49 publications
2
61
0
1
Order By: Relevance
“…6 The high yield of GS in the four studies we identified is consistent with other reports. [53][54][55] Our analyses demonstrate clearly that yields for GS and ES are higher than those of MGP and CGH/CMA for patients with epilepsy. However, we observed highly variable yields across the studies we reviewed, likely due to variable, and sometimes not well-delineated, methods of patient ascertainment and variant interpretation.…”
Section: Discussionmentioning
confidence: 64%
“…6 The high yield of GS in the four studies we identified is consistent with other reports. [53][54][55] Our analyses demonstrate clearly that yields for GS and ES are higher than those of MGP and CGH/CMA for patients with epilepsy. However, we observed highly variable yields across the studies we reviewed, likely due to variable, and sometimes not well-delineated, methods of patient ascertainment and variant interpretation.…”
Section: Discussionmentioning
confidence: 64%
“…Technological advances in genomics and mass spectrometry, leveraging datasets of whole molecule classes (omics), have recently led to a paradigm shift in their use as diagnostic tools. For example, single-layer whole genome sequencing has achieved diagnostic rates of 30-50% (Palmer et al, 2021;Schon et al, 2021), while dual-layer combination with RNA sequencing can improve this by 10-35% (Cummings et al, 2017;Frésard et al, 2019;Gonorazky et al, 2019;Kremer et al, 2017). In spite of these advances a significant number of patients remain undiagnosed and course prediction also remains poor, mainly due to a lack of pathomechanistic understanding and often unclear genotype/phenotype relationships.…”
Section: Mainmentioning
confidence: 99%
“…The future of RD envisions a faster diagnosis thanks to high-throughput Next Generation Sequencing (NGS) technologies as well as artificial intelligence [ 60 ] with the intention of helping clinicians to shorten the time to diagnosis. Several studies demonstrate the utility of whole-exome (WES) [ 61 , 62 ] or whole-genome (WGS) [ 63 , 64 ] sequencing, as well as including other omics, such as RNA-seq or methylation profiles, increasing the diagnostic yield particularly on undiagnosed individuals with a suspected genetic condition [ 65 , 66 ]. Nevertheless, the improvement in diagnostic efficiency comes with several shortcomings, such as cost and time/analysis load [ 24 , 67 ] that are expected to be solved in the near future as technology improves in efficiency.…”
Section: Current Needs and Future Directions Of Genetic Counselling For Rare Diseasesmentioning
confidence: 99%